Antithrombotic therapy in obesity - Badimon, Lina; Hernández Vera, Rodrigo; Padró, Teresa; Vilahur, Gemma (Thrombosis and Haemostasis, 2013)
Clinical management of obese subjects to reduce their risk of suffering cardiovascular events is complex. Obese patients typically require preventive strategies, life-style modifications, and multi-drug therapy to address obesity-induced co-morbidities. Data regarding the effects of excess weight on the pharmacokinetics of most drugs is scarce as these individuals are often excluded from clinical trials. However, the physiological alterations observed in obese patients and their lower response to some antiplatelet agents and anticoagulants have suggested that dosage regimes need to be adjusted for these subjects. In this review we will briefly discuss platelet alterations that can contributeto increased thrombotic risk, analyse existing data regarding the effects of obesity on drug pharmacokinetics focusing on antiplatelet agents and anticoagulants, and we will describe the beneficial effects of weight loss on thrombosis.
Keywords: Obesity; antiplatelets; anticoagulants